Correlations between physiological parameters related with kidney function and minute‐by‐minute urine output. Issue 12 (December 2016) - Otero, Abraham; Cardinal‐Fernández, Pablo; Nin, Nicolás; Rojas, Yeny; Oteiza, Lorena; Garcia‐Carmona, Rodrigo; Caffarena, Gabriel; Lorente, José A.
Abstract: Aim: Recently, devices capable of measuring minute‐by‐minute urine output (UOm) have become available. It is not known how UOm correlates with physiological parameters in normal conditions and in disease states characterized by vascular dysfunction. This paper analyzes correlations between UOm and physiological parameters related to kidney perfusion to provide some insight about UOm pathophysiological interpretation and its relationship with renal blood flow. Methods: We studied 14 male pigs were anesthetized, tracheostomized, and mechanically ventilated. Mean systemic blood pressure (PART ), mean pulmonary artery blood pressure (PPA ), carotid artery blood flow (QCA ), as well as total (QREN ), cortical (QCOR ) and medullary (QMED ) renal blood flows, and the renal resistive index (RRI) were measured or calculated. Animals received an intravenous dose of live E . coli for the induction of sepsis (septic group), or an equivalent amount of normal saline (nonseptic group). Three groups were studied: nonseptic ( n = 6) and septic ( n = 4), both receiving for resuscitation NaCl 0.9% at 4 mL/kg per h; and septic ( n = 4), receiving for resuscitation NaCl 0.9% at 17 mL/kg per h. Animals were monitored for 5 h after the induction of sepsis. Results: In septic animals, UOm was strongly positively correlated with QREN (Kendall's τ = 0.770, P < 0.05), QCOR (τ = –0.566, P < 0.05) and QMED (τ = 0.632, P < 0.05); and negatively correlated with PPA (τ = –0.524, P < 0.05) and RRI (τ = –0.672, P < 0.05). Control animals exhibited weaker correlations. Conclusion: UOm is a good physiological surrogate marker of total and regional renal blood flows and vascular resistance, particularly under septic conditions, probably reflecting glomerulo‐tubular dysfunction in sepsis. Summary at a Glance: Otero et al. have studied in anesthetized, tracheostomized, and mechanicaly ventilated male pigs and found that, when compared with controls, the minute urine output (UOm) in sepsis was a surrogate marker of total and regional renal blood flows and vascular resistance. This observation might reflect glomerulo‐tubular dysfunction in sepsis.